2017
DOI: 10.1038/s41598-017-11718-8
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of high GFI1 expression in AML of normal karyotype and its association with a FLT3-ITD signature

Abstract: Growth Factor Independence 1 (GFI1) is a transcriptional repressor that plays a critical role during both myeloid and lymphoid haematopoietic lineage commitment. Several studies have demonstrated the involvement of GFI1 in haematological malignancies and have suggested that low expression of GFI1 is a negative indicator of disease progression for both myelodysplastic syndromes (MDS) and acute myeloid leukaemia (AML). In this study, we have stratified AML patients into those defined as having a normal karyotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Notably, Gfi1-null mice are viable but are characterized by severe neutropenia with compensatory monocytosis and sensorineural hearing loss (10)(11)(12). Altered GFI1 expression is found in multiple hematologic malignancies, most notably acute myeloid leukemia (AML) and T-cell acute lymphoblastic leukemia (T-ALL) (13)(14)(15)(16)(17). Moreover, loss-offunction mutations in GFI1 cause severe congenital neutropenia (SCN) type 2 and nonimmune chronic idiopathic neutropenia (CIN) of adults, both of which predispose to AML (18,19).…”
mentioning
confidence: 99%
“…Notably, Gfi1-null mice are viable but are characterized by severe neutropenia with compensatory monocytosis and sensorineural hearing loss (10)(11)(12). Altered GFI1 expression is found in multiple hematologic malignancies, most notably acute myeloid leukemia (AML) and T-cell acute lymphoblastic leukemia (T-ALL) (13)(14)(15)(16)(17). Moreover, loss-offunction mutations in GFI1 cause severe congenital neutropenia (SCN) type 2 and nonimmune chronic idiopathic neutropenia (CIN) of adults, both of which predispose to AML (18,19).…”
mentioning
confidence: 99%
“… 89 Recently, Volpe et al analyzed AML with normal karyotype for GFi1 expression and observed that those displaying high expression of this transcription factor have frequent FLT3 ITD and NPM1 mutations, display an FLT3 ITD signature, and exhibit high expression of some leukemia-related genes, such as HOXA9 , MEIS1 , and PBX3 . 90 At variance with the findings of Hönes et al 89 obtained in the whole AML population, in karyotype-normal AML, high GFi1 expression was associated with a worse outcome. 90 …”
Section: Lsd1mentioning
confidence: 84%
“…GFI1 influences prognosis of AML, CML and MPN patients in a dose-dependent manner, and in murine models of human leukemia reduced levels of GFI1 accelerated disease development (911, 14). AML, CML and MPN arise as a result of transformation of HSCs or early hematopoietic progenitors that still possess some degree of stem cell capacity (15).…”
Section: Resultsmentioning
confidence: 99%